Predicting Throwing Performance with Force-Velocity Mechanical Properties of the Upper Limb in Experienced Handball Players (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
Predicting Throwing Performance with Force-Velocity Mechanical Properties of the Upper Limb in Experienced Handball Players